APPLICATION OF CRT (CHINESE REMINDER THEOREM) TO SPEED UP THE PROCESS OF DATA SECURITY ON IMAGE FILES - Syaufi Arbin; Arpan; Eko Hariyanto (Sean Institute, 2022)
The purpose of this study is to use the Chinese Remainder Theorem approach to create a data security application system and to improve the data security of a confidential file, particularly data that uses image files. Observation and literature review were employed in this study to acquire data. The traditional approach is used to share data, in this case a secret message in the form of text. The embedding process and the extraction process are the two fundamental procedures in message insertion utilizing the Least Significant Bit approach. The Least Significant Bit steganography technique was used to replace the secret message bits in the final bit of each color component of the image pixels, according to the results. So that the image size does not change, only one message bit (value 0 or 1) is placed into one color component of the image. Furthermore, the processing time is affected by the size of the file, the length of the key, and the computer processor performance.